Analisis Kemampuan Guru Pendidikan Anak Usia Dini (PAUD) Dalam Menggunakan Media Pembelajaran - Gisca Anugrah Yuhendra; Irfah Zakiya Hamidi; Keisya Najla Kamila; Thia Tabina Fauziah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Learning media is one of the components of learning that has an important role in teaching and learning activities. This study aims to determine the ability of Early Childhood Education (ECE) teachers in designing and using effective learning media. This research method uses a descriptive qualitative approach with questionnaire data collection techniques. The sample of this study were all 11 teachers of TK IT Nur Al-Rahman. The results showed that the knowledge of using learning media for TK IT Nur Al-Rahman teachers mostly had sufficient knowledge about the use of learning media. Teachers as respondents stated that they have designed and used learning media that are effective in delivering learning materials, adjusting to the potential of students and can be used anytime and anywhere.